PERILAKU KONSUMEN DALAM KATEGORI KELAS SOSIAL: PENGAMBILAN KEPUTUSAN KELUARGA - Dewi, Ngesthi Nirmala; ., Indarini; Anandya, Dudi (Journal of Management and Business, 2007)
Social class has been the interesting subject in consumer behavior studies, so does the collective decision making. This study explore the consumer decision making whether as individual or as family regarding some behavior. The study covers five social class range from upper to the lowest social classes. The result shows interesting findings that although all behaviors can be classified into the same categories, they show specific characters for some social classes. The findings also covers the decision making dominance in the family regarding specific product characteristics.